2018
DOI: 10.1111/aji.12978
|View full text |Cite
|
Sign up to set email alerts
|

Granulysin‐mediated apoptosis of trophoblasts in blighted ovum and missed abortion

Abstract: The reduced activation of GNLY-mediated killing might be implicated in the slower rejection of trophoblast cells in BO and MA. A decreased authentic decidual NK cell number could be responsible for low cytotoxicity against trophoblast cells in MA. In BO, trophoblast cells have a higher survival potential due to increased NF-kB expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…cells after T. gondii infection caused an imbalance between inhibitory and activating receptors, thereby contributing to abnormal pregnancy outcomes. The cytotoxic molecules GranzymeA, GranzymeB and Perforin are constitutively produced by NK cells (Trapani et al, 1998;Shirshev et al, 2017;Gulic et al, 2018). Researchers have found that dysfunctional dNK cells release excessive GranzymeB and Perforin which induce pregnancy failure (Trapani et al, 1998;Gulic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…cells after T. gondii infection caused an imbalance between inhibitory and activating receptors, thereby contributing to abnormal pregnancy outcomes. The cytotoxic molecules GranzymeA, GranzymeB and Perforin are constitutively produced by NK cells (Trapani et al, 1998;Shirshev et al, 2017;Gulic et al, 2018). Researchers have found that dysfunctional dNK cells release excessive GranzymeB and Perforin which induce pregnancy failure (Trapani et al, 1998;Gulic et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NK cells respond to inflammatory stimuli and are best known for their role in tumor immunosuppression. Phenotypically, NK cells are defined as CD56 + CD16 + CD3 – in humans [28, 30]. NK cell activity depends on the interplay of their activating and inhibiting receptor repertoire [28, 30].…”
Section: The Role Of Nk Cells In Breast Cancermentioning
confidence: 99%
“…Phenotypically, NK cells are defined as CD56 + CD16 + CD3 – in humans [28, 30]. NK cell activity depends on the interplay of their activating and inhibiting receptor repertoire [28, 30]. After activation, NK cells secrete proinflammatory cytokines such as interferon-γ, tumor necrosis factor-α, granulocyte macrophage colony-stimulating factor, and chemokines (CCL1, CCL2, CCL3, CCL4, CCL5 and CXCL8) that can modulate the function of other innate and adaptive immune cells [29, 31, 32].…”
Section: The Role Of Nk Cells In Breast Cancermentioning
confidence: 99%
See 2 more Smart Citations